2020
DOI: 10.1002/ajmg.c.31807
|View full text |Cite
|
Sign up to set email alerts
|

Early neurodevelopmental and medical profile in children with sex chromosome trisomies: Background for the prospectiveeXtraordinarYbabies study to identify early risk factors and targets for intervention

Abstract: Sex chromosome trisomies (SCT), including Klinefelter syndrome/XXY, Trisomy X, and XYY syndrome, occur in 1 of every 500 births. The past decades of research have resulted in a broadening of known associated medical comorbidities as well as advances in psychological research. This review summarizes what is known about early neurodevelopmental, behavioral, and medical manifestations in young children with SCT. We focus on recent research and unanswered questions related to the risk for neurodevelopmental disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 148 publications
0
51
0
Order By: Relevance
“…Both historic and more recent natural history studies support that the majority of children born with an extra sex chromosome will experience developmental delays in early childhood, including early speech-language or motor delays (Bender et al, 1983;Robinson et al, 1982;Tartaglia et al, 2020). Reduced expressive language and speech sound disorders (e.g.…”
Section: Implications For Schoolmentioning
confidence: 99%
See 3 more Smart Citations
“…Both historic and more recent natural history studies support that the majority of children born with an extra sex chromosome will experience developmental delays in early childhood, including early speech-language or motor delays (Bender et al, 1983;Robinson et al, 1982;Tartaglia et al, 2020). Reduced expressive language and speech sound disorders (e.g.…”
Section: Implications For Schoolmentioning
confidence: 99%
“…Low muscle tone and poor sensorimotor coordination can also present, leading to lagging motor skills, including delayed walking (Martin et al, 2019;Salbenblatt et al, 1987;Salbenblatt et al, 1989). A recent nationwide parental survey indicated that a significant portion of young children with SCAs living in the US receive early intervention (EI) therapies and/or early childhood special education preschool prior to entering kindergarten (Thompson et al, 2020).…”
Section: Implications For Schoolmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, students with SCAs have increased risks for learning disabilities and academic challenges, medical problems and hormone dysfunction, as well as increased risk for psychological disorders that can impact school functioning such as ADHD, ASD, anxiety, and depression (Tartaglia et al, 2020;Urbanus et al, 2020). Natural history studies have documented a pattern of educational struggles and current surveys have shown high rates of early interventions and special education supports in this student population (Bender et al, 1993;Linden & Bender, 2002;Rovet et al, 1996;Thompson et al, 2020).…”
mentioning
confidence: 99%